Flexibility vs. specialisation in ro-ro shipping in the South Baltic Sea - Woxenius, Johan (Transport, 2012)
The trade-off between flexibility and specialisation implies delicate tasks for transport system designers and marketing managers. The outcome of their efforts ranges from highly specialised solutions for a restricted number of users and types of cargoes to very open systems for common use adapted to accommodate a wide variety of transport demands. The purpose of this article is to adapt theories on openness and trade-offs, characterise a selection of flexible and specialised European short sea shipping concepts and analyse how substantial changes in the future character of the competition with road and rail can affect the development of ro-ro shipping in the South Baltic Sea. A matrix with commercial openness and technological openness on the axes is used for categorising sub-segments in the empirical context of the South Baltic Sea. Foreseeable changes in key cost and competition parameters until 2020 are taken into account in discussing potential scenarios. A plausible outcome for the ferry/ro-ro shipping segment is that a branch with slow services for unaccompanied freight will be diverted from the current homogenous market offerings. During the study, the Swedish Orient Line launched a service with these characteristics, which is analysed in a case study.First Published Online: 19 Sep 2012